PENGEMBANGAN EKONOMI MASYARAKAT DESA JONGKONG KANAN MELALUI BUDI DAYA SARANG WALET PERSPEKTIF EKONOMI ISLAM - Abdul Nasir (Adisam Publisher, 2023)
This research aims to analyze the economic development of the Jongkong Kanan Village of the Jongkong community through swallow nests in Jongkong District, Kapuas Hulu Regency. So the focus of this problem is 1. Describe the economic development of Jongkong Kanan Village through swallow nests in Jongkong District, Kapuas Hulu Regency. 2. Analyze the economic development of Jongkong Kanan Village through the swallow's nest from an Islamic Economics perspective. The approach and type of research used is a qualitative approach and the type of research used is descriptive research. Meanwhile, this data collection technique uses observation, interview and documentation techniques. The research results show that: Realizing prosperity and improving a decent life for Muslims is a sharia obligation, which if accompanied by sincerity of intention will rise to the level of worship. The realization of economic development in Islam is through the integration of individual efforts and government efforts. Where the role of the individual is the principle and the role of the government is a complement. In Islam, the state is obliged to protect the interests of society from injustice. The state is also obliged to provide social security so that all society can live a decent life. The development of swallow nests in Jongkong Kanan Village is very beneficial for the people of Jongkong Kanan Village and provides prosperity for the local community, even though swallow nests are close to residential areas, this is not seen by the residents as not a threat but an advantage in cultivating bird nests. swallows, and the profits will be shared by the swallow nest grower for what percentage will be for the environment in Jongkong Kanan Village.